Impact of Economic Policy Uncertainty on the Indian Stock Market : An Empirical Investigation - Kalra, Naman; Gupta, Gaurav (Indian Journal of Finance, 2023)
Purpose : This study examined the impact of economic policy uncertainty on the Indian stock market. Economic policy uncertainty showed that uncertainties persist in the economy and may affect economies, industries, and companies. The stock market of any economy is very volatile, and it can be easily affected by any small changes in the economy on a national and international level. We argued that EPU also significantly affected the Indian stock market. Design/Methodology/Approach : We analyzed the relationship of economic policy uncertainty with stock prices and market volatility using linear and logarithmic regression. Findings : Our study found that economic policy uncertainty had a positive correlation with market volatility and a significant negative relationship with returns on the Indian stock market. Further, EPU had negative impacts on the performance of firms. We also found that economic policy uncertainty did not have a similar impact on every sector. Sectors dealing with discretionary products and services like automobiles were more negatively impacted than sectors like fast-moving consumer goods and pharmaceuticals. Practical Implications : An investor must understand the impact of uncertainties on equity investments and different sectors to make sound decisions during such times. This information can be used both by firms and retail investors to act accordingly when the future trajectory of the economy is uncertain. Also, the authorities should try to reduce such risks as these can negatively impact the economic growth of a country. Originality/Value : This study contributes to the existing literature by examining the impact of economic policy uncertainty on the Indian stock market. Further, this study stated that economic policy uncertainty could be used as a predictive variable in addition to other macroeconomic variables in stock prediction models, making this study unique.